Therapeutic Use of Silymarin in the Management of Suspected Renal - Saad A. Hussain; Intesar T. Numan; Ban H.Khalaf; Talal A. Abdulla (College of Pharmacy University of Baghdad, 2017)
Long-term use of non-steroidal anti-inflammatory drugs (NSAIDs) mostly associated with renal and hepatic adverse effects, and the adjunct use of compounds with potent protective effects, like silymarin, may be one of the choices to avoid these effects. This project was designed to evaluate the protective effect of silymarin against the suspected renal and hepatic injury induced with long term use of NSAIDs; 220 patients with osteoarthritis were randomized into 5 groups and treated with either silymarin 300mg/day alone, piroxicam 20mg/day alone, meloxicam 15mg/day alone or the combination of each of them with silymarin for 8 weeks. The renal and hepatic functions were evaluated before starting treatment and after 8 weeks including assessment of serum levels of urea, creatinine and the activities of the hepatic enzymes alkaline phosphatase (ALP), glutamic-oxalic acid transaminase (GOT) and glutamic-pyruvic acid transaminase (GPT). The results indicated that using NSAIDs alone produced elevation in the markers of renal and hepatic damage that can be successfully prevented or reversed when silymarin adjunctly used with them. In conclusion, silymarin when co-administered with the NSAIDs (piroxicam or meloxicam) decreases their renal and hepatic toxicities in OA patients. Key words: Silymarin; Piroxicam, Meloxicam; Nephroprotection; Hepatoprotection